New Xanthone Glycosides from Comastoma pedunculatum - Qiao, Yongqi; Yuan, Yi; Cui, Baosong; Zhang, Ying; Chen, Hui; Li, Shuai; Li, Yan (Planta Medica, 2012)
Five new xanthone glycosides, comastomasides A–E (1–5), were isolated from aqueous ethanol extracts of the aerial portions of Comastoma pedunculatum. The structures of these compounds were elucidated by spectroscopic analysis methods. Compounds 1–5 were evaluated for their hepatoprotective activity and cytotoxicity against four human cancer cell lines by in vitro assays. Among them, compounds 3 and 5 exhibited potent hepatoprotective activity. However, none of the compounds displayed cytotoxic activity.
Keywords: Comastoma pedunculatum; Gentianaceae; xanthone glycosides; hepatoprotective activity